Impact of digital orthodontics on maxillary protraction with implants in children with skeletal class III: A systematic review and meta-analysis - Fawaz Hassan Alzahrani; Raghu Devanna; Yousef Althomali; Nayef Hassan Felemban; Prashant Manjunath Battepati; Amith V. Holenarasipur (Saudi Dental Journal, 2024)
Objective: The objective of this systematic review is to assess the effectiveness of digital orthodontics in utilizing implants for maxillary protraction as a treatment for skeletal class III malocclusion in children. Materials and Methods: The study was registered with PROSPERO with the number CRD42023407406 on 23/03/2023. We conducted an extensive comprehensive literature search in nine electronic databases, including PubMed, PubMed Central, Scopus, Cochrane databases, Google Scholar, MEDLINE, EMBASE, LILACS, and the Web of Sciences databases. The studies were evaluated for their methodology, the intervention technology used, the outcomes, and their quality. Publication bias assessment was conducted using the Jadad scale and the ROBINS-I assessment tool. Results: We included a total of 17 studies that comprised a total of 376 patients in this analysis. The number of patients and participants fluctuated between 1 and 71, with > 60 % being female. The patients were aged between 1.1 and 19.2 years. We included only nine studies in the meta-analysis, in which we observed a success rate between 71.4 % and 100 % with a 95 % CI of 17.4 ± 2.988 (±17.2 %) [14.412–20.388]. The failure rates, although minimal, ranged from 5.9 % to 28.6 %, with a 95 % CI of 2.3 ± 1.480 (±64.3 %) [0.820–3.780]. Conclusion: The evidence suggests that digital orthodontics is a promising approach for treating children with skeletal class III malocclusion using implants for maxillary protraction. However, further high-quality studies are required for validating our current observations and regulating the stability of treatment outcomes on a long-term basis.